Technological Intensity of Serbian Manufacturing industry in Pre-Covid-19 Period - Nikolic, Ivan (Industrija, 2020)
This paper analyses technological intesity of Serbian manufacturing sector. The key purpose is to identify development of technological advancment groups (high, medium-high, medium-low and low) during the period of 2010-2019. The analysis shows that in 2019 the share of high-tech production areas in the total MVA increased to 5%, which is the best result since 2015. Changes in production correspond to the movement in foreign trade. The coverage of imports by exports of the manufacturing industry, relatively observed in the medium term, is increasing the fastest in the segment of tangible production, which is included in the category of medium-technological complexity. Serbia is not exclusively competitive in the labour intensive stages of production. It is also competitive in a good part of medium-technological complexity production. Finaly, vast FDI inflows and the activities of foreign investors, in good part, drive successful technological restructuring in recent years.
Keywords: Technological intensity and structure, manufacturing industry, value added, export, FDI